Analyzing Biosimilars in Brazil: Comprehensive Specifications of the Regulatory System - Deeksha, Kethareshwara Sujatha; Veeranna, Balamuralidhara; Ravindra, Gowthami Kodlahalli (Indian Journal of Pharmaceutical Education and Research, 2023)
The largest nation in South America, Brazil, is now the world's second-largest market for pharmaceuticals thanks to the country's economic growth. The Brazilian Health Surveillance Agency, also known as the National Agency for Health Surveillance (Agencia Nacional de Vigilancia Sanitaria - ANVISA), was founded in 1999 with the primary objective of protecting and strengthening public health surveillance over Brazilian products and services. Biological products, also known as biopharmaceuticals, are medications that are derived from biological systems and then created utilizing contemporary biotechnological techniques. These biological products are very different from traditional synthetic drugs in a number of important respects. Biosimilars are required to satisfy a variety of regulatory requirements before being given permission to enter the market in various regions. Other issues that are related to this need to be established by national authorities. These issues include interchangeability, labelling, and prescription information. The Brazilian health monitoring agency follows the fundamental criteria established by the World Health Organization for evaluating bio-similarity; nevertheless, it does not make use of the name "biosimilar." The objective of this article is to present the Brazilian biosimilar law.
Keywords: ANVISA; Regulations; Guidelines; Biosimilars; Pathway